Imperfection method based on optical fiber for alcohol content detection sensor - Muhammad Yunus; Syahdad Aziz; Bunga Tang; Yusuf H. Usman; Irsan Irsan; Septiana Kurniasari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Testing of optical fiber-based sensors using the imperfection method to detect alcohol contents. The sample results from mixing alcohol and distilled water to produce eight samples with an alcohol content level from 0% to 70%. The greater alcohol content causes the output power of the sensor to decrease due to the increase in the refractive index of alcohol content around the sensor. An increase in the refractive index of alcohol content causes power losses to increase, resulting in lost light intensity being transmitted in optical fiber-based sensors. Power losses are increasing to produce the best characteristics of the sensor. The best sensor is shown in the Gamma configuration at imperfection 3 with a sensitivity value of 0.346 µW/%. The imperfection method is suitable for determining the characteristics of optical fiber-based alcohol detection sensors because it has a high sensitivity.